2013
DOI: 10.5304/jafscd.2013.033.008
|View full text |Cite
|
Sign up to set email alerts
|

Community Food Systems: Strengthening the Research-to-Practice Continuum

Abstract: Growing public interest in links between food, health, and the environment has sparked exponential growth in local and regional food system projects. Along with local experimentation has come an accompanying surge in related academic research. Are we learning what we need to know to expand the impact of the work? This paper introduces a new community food systems bibliography as a tool to help build usable knowledge. Drawing on a set of literature reviews prepared by students in a University of California Davi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In particular, comparative case studies that involve both researchers and community practitioners in design, data gathering and analysis, can begin to address some of the social justice challenges faced in UA settings 67 . Beyond providing a source of accessible, science-based information for urban farmers and policy makers, UC ANR and similar institutions can play an important role in contributing to the growing body of knowledge on UA and its impacts on communities.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
“…In particular, comparative case studies that involve both researchers and community practitioners in design, data gathering and analysis, can begin to address some of the social justice challenges faced in UA settings 67 . Beyond providing a source of accessible, science-based information for urban farmers and policy makers, UC ANR and similar institutions can play an important role in contributing to the growing body of knowledge on UA and its impacts on communities.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
“…In both cases, the answer is a lot, but with limits. Campbell, Carlisle-Cummins and Feenstra (2013) note it is important to attempt to bridge the gap between research and practice in community food systems. The learning outcomes from this study emerged from the lived experience of being a CSA member in a particular place for a year, so the study was practice-led.…”
Section: Resultsmentioning
confidence: 99%
“…So this research, following Fuller (1999), was not so much about 'going native' as about being aware of the issues and benefits of being as 'native' as any other newcomer in a CSA established by a community of newcomers. As Campbell et al(2013)stated, "practitioners need to be active partners in advancing and generating new knowledge. This might include putting greater priority on fostering partnerships between practitioners and researchers to design and implement research projects on identified challenges"(p. 133).…”
Section: Resultsmentioning
confidence: 99%
“…The biggest interest is to study alternative farming techniques [77] that have been studied very little by agronomists until now, including synecoculture, permaculture [65,64], and bio-intensive micro-farming [76]. The platform also allows the community explore new technological tools and sensors to monitor and optimise these cropping techniques, using a collaborative approach [70,75]. ‡ See https://p2pfoodlab.net/CitizenSeeds/experiments/4.html (Peter Hanappe)…”
Section: Future Developmentsmentioning
confidence: 99%